2008
DOI: 10.1124/jpet.108.138008
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Morphine and a Blocker of Glycogen Synthase Kinase 3β, SB216763 [3-(2,4-Dichlorophenyl)-4(1-methyl-1H-indol-3-yl)-1H-pyrrole-2,5-dione], via Inhibition of the Mitochondrial Permeability Transition Pore

Abstract: Morphine has been shown to protect the myocardium against ischemia-reperfusion injury through inhibition of glycogen synthase kinase-3␤ (GSK-3␤). Given that GSK-3␤ is known to modulate the mitochondrial permeability transition pore (mPTP), we investigated the role of mPTP in the cardioprotective effect of morphine and the GSK-3␤ inhibitor SB216763 [SB; 3-(2,4-dichlorophenyl)-4(1-methyl-1H-indol-3-yl)-1H-pyrrole-2,5-dione] during ischemia-reperfusion. Both morphine (0.3 mg/kg) and SB (0.6 mg/kg) reduced infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 36 publications
3
80
0
1
Order By: Relevance
“…Some animals were administered vehicle control (1% DMSO in 0.9% NaCl solution) and 70 or 600 μg/kg SB216763 i.v. (SigmaAldrich Chemical Co.) 5 min before coronary artery occlusion, as indicated (3,41). In some animals, TAT 47-57 -conjugated RRNYRRNY or TAT 47-57 -conjugated RRPPYN control was administered by an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Some animals were administered vehicle control (1% DMSO in 0.9% NaCl solution) and 70 or 600 μg/kg SB216763 i.v. (SigmaAldrich Chemical Co.) 5 min before coronary artery occlusion, as indicated (3,41). In some animals, TAT 47-57 -conjugated RRNYRRNY or TAT 47-57 -conjugated RRPPYN control was administered by an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Ventricular cardiomyocytes were isolated using enzymatic digestion according to previously described procedure. 35,36 Briefly, WT mice were anesthetized with pentobarbital (70 mg/kg) (Sanofi Santé Animale, Libourne, France) and the heart was quickly harvested and retrogradely perfused at 37°C for 6-8 min with a perfusion buffer (113 mM NaCl, 4.7 mM KCl, 0.6 mM KH 2 PO 4 , 0.6 mM Na 2 HPO 4 , 1.2 mM MgSO 4 , 12 mM NaHCO 3 , 10 mM KHCO 3 , 10 mM HEPES, 30 mM Taurine, pH 7.4) containing 10 mM 2,3-butanedione, 5.5 mM glucose, 12.5 μM CaCl 2 , 0.1 mg/ml of liberase (Roche) and 0.14 mg/ml trypsin (Sigma). Isolated myocytes were then maintained in culture in laminin-(10 μg/ml) precoated dishes with M199 medium (Invitrogen) and allowed to attach for 2 h before analysis.…”
Section: Gsk3β Regulates Ca 2+ Transfer At Mams L Gomez Et Almentioning
confidence: 99%
“…Although pre-clinical studies except for one using mice 55,57,60,72,73,75 have shown that inhibitors of GSK-3β could limit infarct size in animal models of AMI, efficacy of the GSK-3β inhibitors has not yet been assessed in human cardiac tissues. However, protection of the human heart was reportedly achieved by an inhibitor of mPTP, cyclosporine A, 110 ischemic preconditioning, [113][114][115] and postconditioning.…”
Section: Gsk-3β Inhibitors For Clinical Applicationmentioning
confidence: 99%
“…Direct inhibition of GSK-3β by the use of structurally different pharmacological inhibitors (SB-216763, lithium chloride) administered before either ischemia or reperfusion limits infarct size. 55,57,60,72,73 It is interesting to note that inhibitors of GSK-3β increase the level of phospho-GSK-3β, which is explained by GSK-3β-mediated positive regulation of protein phosphatase-1 (Figure 3). 74 Nevertheless, these findings support the notion that inactivation of GSK-3β by phosphorylation at Ser9 is a common mechanism of protection of cardiomyocytes against necrosis in many cardioprotective interventions.…”
Section: Gsk-3β and Tolerance Of Cardiomyocytes To Necrosismentioning
confidence: 99%